Persimmon leaf extract alleviates chronic social defeat stress-induced depressive-like behaviors by preventing dendritic spine loss via inhibition of serotonin reuptake in mice - Hui Yu; Shumin Shao; Junnan Xu; Haibiao Guo; Zhangfeng Zhong; Jiangping Xu (BMC, 2022)
Abstract Background Fresh or dried Persimmon leaves (Diospyros kaki Thunb.) exhibit preventive effects on cardiovascular and cerebrovascular diseases. However, their antidepressant effects and underlying mechanisms are unclear. Thus, we investigated mechanisms responsible for Persimmon leaf extract (PLE) activity on chronic social defeat stress (CSDS)-induced depressive-like behaviors in mice. Methods CSDS was used as a mouse model of depression. We performed the sucrose preference test (SPT), forced swim test (FST), and tail suspension test (TST) to identify depressive-like behavior. Spine density and dendritic morphology were assessed using Golgi staining. Neurochemicals were quantified by microdialysis, doublecortin by immunofluorescence, and cAMP using an ELISA kit. Finally, the levels of cortical proteins of phosphorylated cAMP-response element binding protein (CREB), brain-derived neurotrophic factor (BDNF), postsynaptic density synapsin-1 and protein 95 (PSD95) were quantified by western blot. 16S rRNA gene sequencing was used to detect fecal microbiota. Results Treatment of CSDS-subjected mice with PLE (30.0-60.0 mg/kg, i.g.) enhanced sucrose preference, decreased immobility times in the TST and FST but did not affect locomotor activity. Furthermore, persistent social defeat stress decreased dendritic spine density and dendritic length in the brain, as well as decreased PSD95 and synapsin-1 expression. PLE, interestingly, inhibited dendritic spine loss and increased synaptic protein levels. PLE also increased brain levels of 5-HT, cAMP, phosphorylated (p)-CREB, BDNF, PSD95, and synapsin-1 in mice subjected to CSDS. Furthermore, PLE increased their doublecortin-positive cell count in the hippocampal dentate gyrus. CSDS mice represented a distinct fecal microbiota cluster which differed compared with normal C57BL/6J mice, and the phenotype was rescued by PLE. Conclusions PLE alleviated CSDS-induced depressive behaviors and spinal damage by suppressing serotonin reuptake and activating the cAMP/CREB/BDNF signaling pathway. Simultaneously, PLE influenced the composition of the fecal microbiota in CSDS-subjected mice.